Effect of topical use of mitomycin C and 5-fluorouracil on the closure time of myringotomies created by radiofrequency unit - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2009)
Conclusion: Both mitomycin C (MC) and 5-fluorouracil (5-FU) had a significant effect in prolonging the patency rate of radiofrequency myringotomy. Objective: To compare the effect of topical use of MC and 5-FU on the closure time of myringotomies created by a radiofrequency unit. Materials and methods: Myringotomies were performed using a radiofrequency unit on 80 tympanic membranes of 40 rats. Rats were divided into two study groups and one control group. MC (0.4 mg/ml) and 5-FU (50 mg/ml) pledgets were applied topically in the right ears (study groups, 20 ears each) for 10 min and saline pledgets in the left ears (control group, 40 ears). Animals were monitored using otomicroscopy weekly and patency rates were recorded until myringotomy closure. Results: The mean patency times were 4.85 weeks for the MC group and 3.90 weeks for the 5-FU group. The mean patency rate for the control side was 1.30 weeks. The log-rank test revealed both study groups to have a significantly longer patency time than the control group (p <0.0001). Although the patency rate was found to be higher in the MC-treated group than the 5-FU-treated group, this difference was not statistically significant (p > 0.05).
Keywords: Radiofrequency; 5-fluorouracil; mitomycin C; myringotomy; TYMPANOSTOMY TUBES; LASER MYRINGOTOMY; OTITIS-MEDIA; EAR